Epidemiological and Clinical Profile of Cleft Lip and/or Palate in Mbujimayi: A Cross‐Sectional Study - Trésor Kabuya Kabamba; Eugène Mukeba Bamusua; Pascal Cimpaka Kabeya; Pascal Kayembe Shambuyi; Micheline Nyembo Epupwa; Didier Mubenga Katende; Séraphin Binene Katulondi; Henry‐Benjamin Tshimanga Kabeya; Jenny Nshimba Kabemba; Joël Manyonga; Joseph Luboya Kabila; Hubert Kabanga Ngandu; et al. (Health Science Reports, 2026)
ABSTRACT Background and Aim Cleft lip and/or palate (CLP) is the most common craniofacial malformation worldwide, with significant geographic and socioeconomic disparities. In Mbujimayi, DRC, no prior data have been published on its prevalence or clinical presentation. This study aimed to determine the epidemiological and clinical profile of CLP in Mbujimayi. Methods This was a cross‑sectional study conducted at the University Clinics of Mbujimayi between March 2023 and July 2025. A total of 54 patients with CLP were included. Ethical approval was obtained. Data were collected on demographic characteristics, anatomical types of CLP, and associated complications. Results Unilateral cleft lip was the most frequent anatomical type, predominantly affecting the left side (48.1%). The mean age of patients was 5.5 years, with extremes ranging from 0.5 to 20 years. Feeding difficulties (40.7%), speech disorders, malnutrition, and social integration challenges (27.8%) were among the most common complications. A family history of CLP was reported in 13.0% of cases, and one associated malformation (cryptorchidism) was noted. The absence of a regional registry and reliance on free surgical campaigns limited the assessment of prevalence and postoperative outcomes. Conclusion CLP is relatively common in Mbujimayi and is accompanied by significant clinical and psychosocial complications. Its management remains a major challenge in this resource‐limited setting. The establishment of a congenital malformation registry and structured follow‐up programs is essential to improve care and guide future research. Trial Registration Not applicable.